Food safety knowledge, attitude and practice awareness among consumer at Intan, Kemaman / Tuan Nurbaiyah Tuan Hamid & Faziana Ali Rajamani - Tuan Hamid, Tuan Nurbaiyah; Ali Rajamani, Faziana (2017)
This study is to identify the level and the common variable of food safety knowledge, attitude and practice awareness among consumer. This study use quantitative study and were involved 169 respondent to fill up questionnaires and it has been distributed randomly to consumer at INTAN, Kemaman. The result indicate beta coefficient, the most variable awareness among consumer is practice with -.195 with total average mean 3.84 follow by knowledge 0.117(average 3.61) and attitude -.001(average 3.51).The finding explained that the most of consumer at INTAN ,Kemaman knows better on common practice for food hygiene such as washing hand, eating doneness of meat and using hygiene cutleries and crockeries compare to other variables